The Effect of Intellectual Intelligence and Learning Behavior on Accounting Understanding in Accounting Students of Medan State University - M. Doli Indra Nasution; Anggi Pratama Nasution; Puja Rizqy Ramadhan (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This research is based on determine or empirical testing of intellectual intelligence and learning behavior towards the understanding of accounting. The method of this research is the survey method with a questionnaire by taking a sample of 83 students at the Medan State University. The method used in this study was purposive sampling. This research used data analysis method with SPSS software. The results of the study used multiple linear regression analysis showed that emotional intelligence and learning behavior had a significant effect on the understanding of accounting.